2000
DOI: 10.1089/neu.2000.17.185
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Widespread Microglial Activation Induced by Traumatic Brain Injury in Rat Brain Slices

Abstract: In order to assess the role of circulating blood in early microglial activation after traumatic brain injury (TBI), controlled cortical impact injury was applied to adult rat brain slices (400 microm in thickness) and the microglial response was examined. The complement receptor (CR3) expression and morphological transformation of the microglia were evaluated by OX42 immunohistochemistry. At 5 min following injury, activated microglia with intense CR3 expression appeared throughout the hemisphere on the injure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(47 citation statements)
references
References 29 publications
1
46
0
Order By: Relevance
“…Several previous studies have shown that brain resident phagocytes (microglia) become activated in CNS tissue slice preparations, presumably in response to neuronal injury and death (Smith et al, 1990;Brockhaus et al, 1996;Hailer et al, 1996;Czapiga and Colton, 1999;Koshinaga et al, 2000;Stence et al, 2001). Although by 1 DIV, most microglia had a morphological appearance of being fully activated, our time-lapse observations showed that individual microglia differed dramatically in their motile behaviors.…”
Section: Motility States Of Activated Microgliamentioning
confidence: 45%
“…Several previous studies have shown that brain resident phagocytes (microglia) become activated in CNS tissue slice preparations, presumably in response to neuronal injury and death (Smith et al, 1990;Brockhaus et al, 1996;Hailer et al, 1996;Czapiga and Colton, 1999;Koshinaga et al, 2000;Stence et al, 2001). Although by 1 DIV, most microglia had a morphological appearance of being fully activated, our time-lapse observations showed that individual microglia differed dramatically in their motile behaviors.…”
Section: Motility States Of Activated Microgliamentioning
confidence: 45%
“…6) In addition to the above progressive neurodegeneration in the CNS, microglial activation is proposed to be involved in the secondary damage following the primary damage after traumatic brain injury. 7) Microglial activation is also believed to play an important role in pathological pain mechanisms such as nociceptive abnormality and hyperalgesia. 8) Even in psychiatric illnesses, it is reported that mononuclear phagocytes accumulate in the cerebrospinal fluid of schizophrenic patients during acute psychotic episodes, 9) and microglial activation is often observed in the postmortem pathohistologic examination of patients with schizophrenia.…”
Section: Microglial Activation In Various Neuro-logical Diseasesmentioning
confidence: 99%
“…In brain donors and experimental animal models, TBI has been associated with increased reactivity of microglia [81,82]. Microglia are the resident macrophages of the brain.…”
Section: Inflammatory Changesmentioning
confidence: 99%